A review of new knowledge on tail biting and tail docking : Update on the 2015 report 'Practical solutions to reduce tail biting in NI pig herds'.: Update on the 2015 report 'Practical solutions to reduce tail biting in NI pig herds'. (2019) - Buijs. S; Muns, R
No abstract available